Evidentiality in Modern Standard Arabic: A Linguistic Investigation - Hoshan, A.; Sadkhan, R. (2019)
Abstract Evidentiality is a newly-fledged topic in linguistic studies which has gained a new terrain only recently. It refers to the speaker’s coding of the source of information. Evidentiality falls into two types: direct and indirect. The former refers to the speaker’s physical sensory evidence of the situation, where the speaker bases his evidence on his visual and non-visual senses, while the latter entails that the speaker bases his evidence on inferential or reported evidence. Inferential evidentiality can be assumptive in that the evidence is built upon the speaker’s past knowledge and personal experience, or deductive, where the speaker deduces the situation according to the results of the action. Reported evidentiality is concerned with the source of evidence and information the speaker has got from some other source(s), which can be quotative, where the speaker reports the original words of the speaker, or hearsay, in which the speaker has got his evidence from other unknown sources of evidence such as rumour, gossip, and folklore. This study investigates the types and sub-types of evidentiality in Standard Arabic. Evidentiality in Arabic has not been investigated in depth in previous studies, although Arabic has mechanisms for encoding it via a variety of ways. Through a detailed morpho-syntactic and semantic analysis following Palmer’s (2001) model, it was concluded that Arabic is a language which encodes evidentiality in its types and sub-types via a variety of ways such as verbs, adverbs or adverbial / linguistic expressions that encode the meaning of evidentiality. These evidentiality markers include perception verbs, (?af’aalul-šu’uur/?al?iḥsaas /?alḥawaas), supposition verbs (verbs of ?al-đanni), verbs of hearts, (?af’aalul-quluubi), i.e. ?af’aalul-yaqiini (verbs which indicate knowledge and complete truthfulness) and ?af’aalul-rujḥaani, i.e. verbs which indicate potential truthfulness, lexical verbs / expressions, the perfect forms of verbs,the passive constructions as well as mirativity. Some of these markers indicate direct evidentiality types and indirect evidentiality (inferential and reported) or sometimes both of them. The findings of the study have showed that evidentiality in Modern Standard Arabic exists as a separate category and it is distinct from epistemic modality although they sometimes overlap to encode evidential meaning in some contexts.
This is an book written in English.